Asymmetry and thigh muscle coactivity in fatigued anterior cruciate ligament-reconstructed elite skiers - Jordan, M. J.; Aagaard, P.; Herzog, W. (Medicine & Science in Sports & Exercise, 2017)
Purpose: The acute effects of fatigue on functional interlimb asymmetry and quadriceps/hamstring muscle activity levels, including preparatory coactivation during squat jump takeoff and landing, were evaluated in elite alpine ski racers with/without anterior cruciate ligament reconstruction (ACLR).